Randomised clinical trial in women with Recurrent Vulvovaginal Candidiasis: Efficacy of probiotics and lactoferrin as maintenance treatment. Issue 4 (20th February 2019) - Russo, Rosario; Superti, Fabiana; Karadja, Eugen; De Seta, Francesco
Summary: Background: Vulvovaginal candidiasis (VVC) is a recurrent vaginal condition in childbearing women. Objectives: The aim of this study was to assess the efficacy of an oral formulation containing Lactobacillus acidophilus GLA‐14, Lactobacillus rhamnosus HN001 and bovine lactoferrin on symptoms and recurrence of VVC as adjuvant therapy to topical clotrimazole. Patients/Methods: Forty‐eight women positive for C. albicans, symptoms of VVC and documented history of recurrences were randomised into 2 groups receiving verum or placebo (2 capsules/day for 5 days followed by 1 capsule/day for additional 10 days) as adjuvant treatment to clotrimazole (induction phase) followed by a maintenance cycle of 6 months (1 capsule/day verum or placebo for 10 consecutive days each month). Symptoms, overall cure rate and recurrence rate were assessed. Results: After clotrimazole therapy, a significant improvement of symptoms was shown in both groups. However, only women treated with probiotics and lactoferrin showed a significant improvement of itching and discharge at 3 and 6 months. During the six‐month follow‐up, recurrences were significantly less in the intervention group vs placebo (33.3% vs 91.7% after 3 months and 29.2% vs 100% after 6 months). Conclusions: The results show that the investigated lactobacilli mixture in combination with lactoferrin represents a safe and effective adjuvant approach for reducing symptoms and recurrences of RVVC.